Keputusan Akuisisi dan Merger Atas Profitabilitas GoTo Group - Sephiani, Dina; Rokhaminawanti , Ersri (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
The issue of profitability should be given particular consideration because it is necessary for the business to remain profitable in order to continue operating. Tokopedia chose to work together (merge) with Gojek to become GoTo in order to contend in the digital economy. After being acquired by Gojek, Tokopedia became a subsidiary of Gojek. This study tends to ascertain the disparity in profitability between the GoTo Group's acquisition and merger within the 2018–2023 timeframe. A descriptive quantitative approach is the research methodology employed. PT GoTo Gojek Tokopedia Tbk served as the study's sample, and the five research variables were ROA, ROE, NPM, GPM, and OPM. Descriptive statistical analysis, one-sample kolmogorov-Smirnov normality testing, and paired sample t-test hypothesis testing were used to analyze the data. The factors ROA, ROE, NPM, GPM, and OPM did not significantly differ, according to the data.